Caracterização morfológica e distribuição dos Anfisbênios (Squamata: Amphisbaenia) da Amazônia Brasileira - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
The Amphisbaenia is the least-diversified group of Squamata reptiles, with 197 known species. Of these, 74 occur in Brazil. Although there have been improvements in recent years, general knowledge of the group still require data that facilitates identification and characterization of species. The current study was undertaken in order to bring together data on the external morphology and geographical distribution of amphisbaenid species in the Brazilian Amazon. To this end 57 meristic and morphometric characters were analysed from 709 specimens from a variety of scientific collections. Twenty-two species of amphisbaenids were recorded as occuring in the Brazilian Amazon, making it the biome with the third-greatest amphisbaenid diversity in Brazil. Eight species of amphisbaenid (36.3% of the biome´s diversity for this group) have distributions restricted to Amazon: Amphisbaena brasiliana, A. caiari, A. cunhai, A. michelli, A. slevini, A. tragorrhectes, A. vanzolinii and Mesobaena rhachicephala. The distribution of Amphisbaena kraoh was extended into the Amazon basin (the species was previously only known from the cerrado). Three new geographical records were recorded from the analysed sample: Amphisbaena alba for the state of Acre; Amphisbaena caiari, previously known only from the type locality in Rondônia, was recorded for the first time in Pará; and Mesobaena rhachicephala, known only from its type locality in Pará, was recorded for the state of Amazonas. The character variation in 13 of the 22 analysed species was extended, allowing more accurate identification of these species in the future. Additionally, we present a key for species of amphisbaenids from Brazilian Amazon.
Keywords: Amphisbaenidade; Morfologia; Taxonomia; CNPQ::CIÊNCIAS BIOLÓGICAS; GENÉTICA E CONSERVAÇÃO DA BIODIVERSIDADE